IDENTIFIKASI SIFAT FISIKA TANAH PADA PENGGUNAAN LAHAN KAKAO DI INSTALASI PENELITIAN DAN PENGKAJIAN TEKNOLOGI PERTANIAN DESA SIDONDO III - Risaldi, Sahrul; Pata’dungan, Yosep Soge; Zainuddin, Rachmat (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2023)
The aim of this research was to investigate the physical characteristics of soil in cocoa plantations at the Agricultural Technology Research and Assessment Installation of Sigi Biromaru Sub District, Sigi District. Two locations were selected for soil sampling, based on the age of the cocoa plants, specifically 20 years and 25 years. At each location, ten soil samples were collected - five undisturbed and five disturbed samples. The soil analysis was performed at the Laboratory of Soil Science, Faculty of Agriculture, Tadulako University, spanning from August to September 2021. The findings indicated that the 20-year-old cocoa plantation had soil predominantly with a loamy sand texture, heavy bulk density, very poor porosity, moderate organic matter content, and moderate permeability. Whereas, the 25-year-old cocoa plantation exhibited clay-dominated soil with heavy bulk density, very poor porosity, moderate organic matter content, and slightly slow permeability.